2020
DOI: 10.3389/fped.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenic Missense Variant (c.1617G>A, p.Met539Ile) in UBA1 Causing Infantile X-Linked Spinal Muscular Atrophy (SMAX2)

Abstract: Background: Infantile X-linked spinal muscular atrophy (SMAX2) is a rare type of spinal muscular atrophy associated with UBA1 variants.Methods: Clinical imaging and neurophysiological tests were performed on a Chinese patient with SMAX2. Further, focused panel sequencing of UBA1 was carried out on samples of both the proband and his maternal relatives.Results: The proband, a 4-year-old boy with the SMAX2 phenotype, suffered from reduced exercise capacity since infancy. His other symptoms included speech diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The study in mice with SMA1dependent SMA showed that AAV9-UBA1 gene therapy improved body weight, lifespan, and motor performance in mice [Powis et al, 2016] ). The missense variant c.1617G>A was also found in 3 individuals in a family described by Wang et al [2020]. These patients were milder affected when compared to other molecularly confirmed patients.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The study in mice with SMA1dependent SMA showed that AAV9-UBA1 gene therapy improved body weight, lifespan, and motor performance in mice [Powis et al, 2016] ). The missense variant c.1617G>A was also found in 3 individuals in a family described by Wang et al [2020]. These patients were milder affected when compared to other molecularly confirmed patients.…”
Section: Discussionmentioning
confidence: 66%
“…The majority of the cases previously reported had areflexia, progressive muscle weakness, and hypotonia with early onset. Five patients reported by Wang et al [2020] differed from the other patients by a long life span, dysarthria, mild muscle weakness, late-onset age, no bone fractures, contractures, respiratory distress, and no progression. Neuropathy was detected in approximately 33% of previously reported cases.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations